Conjugated Bisphenol A (BPA) in maternal serum in relation to miscarriage risk - Lathi, Ruth B. (Fertil Steril, 2014)
OBJECTIVE: To examine the relationship between maternal serum Bisphenol-A (BPA) concentration at the time of the missed period and miscarriage risk. DESIGN: Retrospective cohort of prospectively collected serum samples. SETTING: Academic fertility center. PATIENTS: Women presenting for early pregnancy monitoring with singleton pregnancies. INTERVENTION: Stored serum samples from 4-5 weeks gestation were analyzed for conjugated serum BPA concentrations. MAIN OUTCOMES: Live birth, miscarriage, and chromosome content of miscarriage. RESULTS: Of the 115 included subjects, there were 47 live births and 68 clinical miscarriages (46 aneuploid and 22 euploid). Median conjugated BPA concentrations were higher in women with miscarriages than those with live births (0.101 vs 0.075 ng/ml). Women with the highest quartile of conjugated BPA had an increased relative risk of miscarriage (1.83, 95% CI 1.14-2.96) compared to women in the lowest quartile. We found a similar increase risk for both euploid and aneuploid miscarriages. CONCLUSIONS: Maternal conjugated BPA was associated with higher risk of aneuploid and euploid miscarriage in this cohort. The impact of reducing individual exposures on future pregnancy outcomes deserves further study.